Relationship between C-Reactive Protein Levels and Preeclampsia in Pregnant Women - Hartatiek Nila Karmila; Nathalya Dwi Kartika Sari; Ika Mardiyanti; Nur Sophia Matin (Ikatan Dokter Indonesia Wilayah Jawa Timur, 2025)
Introduction: Preeclampsia remains a major contributor to maternal morbidity and mortality worldwide, including in Indonesia. Increasing evidence suggests that inflammation plays an important role in its development. C-reactive protein (CRP), an easily accessible inflammatory marker, has been proposed as a potential indicator for early identification. This study aimed to examine the association between CRP levels and preeclampsia in pregnant women. Material and Methods: A case–control study was conducted at RSI A. Yani Surabaya between August and October 2022. Fifty pregnant women beyond 20 weeks of gestation were enrolled, consisting of 25 normotensive and 25 preeclamptic participants. CRP levels were measured using the ichromsa™ system following standard laboratory procedures. Data were analyzed using the Mann–Whitney U test with a significance level of p<0.05. Results: The mean maternal age was slightly higher in the preeclampsia group. Most participants were in the late third trimester. CRP levels differed significantly between groups, with higher values observed among women with preeclampsia (p<0.001). A greater proportion of preeclamptic women had CRP concentrations ≥5 mg/L. Conclusion: This study demonstrates a significant difference in CRP levels between normotensive and preeclamptic pregnancies, supporting the role of inflammation in the condition. However, given the limited sample size and lack of adjustment for confounding factors, the findings should be interpreted cautiously. Larger studies with broader analytical approaches are needed before CRP can be considered for clinical screening or risk stratification.